2019
DOI: 10.3748/wjg.v25.i48.6949
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tumor thrombotic microangiopathy of hepatocellular carcinoma: A case report and review of literature

Abstract: BACKGROUNDPulmonary tumor thrombotic microangiopathy (PTTM) is a rare condition in patients with hepatocellular carcinoma (HCC); to date, few cases have been reported. While hepatic dysfunction has been focused on the later stages of HCC, the management of symptoms in PTTM is important for supportive care of the cases. For the better understanding of PTTM in HCC, the information of our recent case and reported cases have been summarized.CASE SUMMARYA patient with HCC exhibited acute and severe respiratory fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…It has been previously reported that VEGF is being expressed by tumour cells in PTTM cases, as well as tissue factor (TF) and platelet-derived growth factor (PDGF) [5]. The expression of TF and PDGF can lead to hypercoagulation state causing disseminated intravascular coagulation (DIC) [4,7]. This mechanism provokes PH by inducing the remodelling of pre-capillary and post-capillary pulmonary vessels [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously reported that VEGF is being expressed by tumour cells in PTTM cases, as well as tissue factor (TF) and platelet-derived growth factor (PDGF) [5]. The expression of TF and PDGF can lead to hypercoagulation state causing disseminated intravascular coagulation (DIC) [4,7]. This mechanism provokes PH by inducing the remodelling of pre-capillary and post-capillary pulmonary vessels [8].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to narrowing and occluding of small pulmonary vessels until pulmonary hypertension, dyspnea, respiratory failure develop [1,6]. A major part here is played by vascular endothelial growth factor (VEGF) [4]. It has been previously reported that VEGF is being expressed by tumour cells in PTTM cases, as well as tissue factor (TF) and platelet-derived growth factor (PDGF) [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism is caused by tumor cells being spread hematogenously, where the cells will lodge into the pulmonary arteries. This is known as pulmonary tumor thrombotic microangiopathy (PTTM), and it results in thrombus formation within the pulmonary arteries, leading to occlusion of the vessels [ 6 ]. Finally, in a primary or secondary lung malignancy, such as in this patient, PTE can be caused by local invasion and occlusion of the pulmonary arteries [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The staging of primary tumors such as liver, breast, stomach, kidney, and prostate carcinoma can assess the risk of developing pulmonary tumor embolism, justifying the higher risk of embolism in advanced-stage cancer. Generally, clinicians correlate the risk of pulmonary tumor embolism with advanced-stage tumors that usually metastasize to the lungs [ 4 ]. PE along with liver metastatic carcinoma is uncommon, and a recent study identified that out of 658 autopsies, 20 patients had pulmonary tumor emboli.…”
Section: Introductionmentioning
confidence: 99%